PENGARUH LEVERAGE, LIKUIDITAS, DAN KUALITAS AUDIT TERHADAP PENGHINDARAN PAJAK - Mirda Thalia Khairunnisa; Ade Imam Muslim (Jurnal Riset Keuangan dan Akuntansi, 2020)
This research aims to determine the effect of leverage, likuidity, and audit quality to tax avoidance in manufacturing company listed on Indonesian stock exchange. Independent variable in this research is leverage, likuidity, and audit quality, while dependent variable in this research is tax avoidance. This research using descriptive method. Population in this research is 130 manufacture companies Listed on Indonesian Stock Exchange during period 2016-2019. Sample in this research determined using purposive sampling technique. The analytical method used is multiple linier analysis. The result of this research indicate that leverage and likuidity has an effect on tax avoidance, while audit quality hasn’t an effect on tax avoidance. Simultaneously the variable leverage, likuidity and audit quality has an effect on tax avoidance. Keywords: Leverage, Likuidity, Audit Quality and Tax Avoidance